THE LEVEL OF STUDENTS’ METACOGNITION THINKING DURING ONLINE LECTURES IN THE COVID-19 PANDEMIC - Mohammad Archi Maulyda; Lalu Hamdian Affandi; Vivi Rachmatul Hidayati (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2021)
Abstract:During the pandemic, the lectures conducted online tend to make the students not serious about attending the lectures. The absence of direct supervision from lecturers is one of the reasons why this can occur. Thus, the researchers assume that the level of students’ metacognition who follow the online lectures is still low. Therefore, the objective of this study is to analyze the level of students’ metacognition during online lectures that have been carried out. The researchers used a qualitative-descriptive research approach with online form filling method. The research subjects were 120 students who had taken online courses for at least 8 meetings or 2 months. The results showed that 83 students were at the lowest metacognition level (Tacit Use), while the students who were at the highest level of metacognition were 2 students (Reflective Use). Thus, it is inferred that the students’ metacognition level during the online lectures is still very low.Abstrak:Selama pandemi, perkuliahan dilaksanakan secara online, hal ini mengakibatkan adanya kecenderungan mahasiswa menjadi tidak serius menghadiri perkuliahan. Tidak adanya pengawasan langsung dari dosen menjadi salah satu penyebab hal tersebut bisa terjadi. Dengan demikian peneliti berasumsi bahwa tingkat metakognisi mahasiswa yang melaksanakan perkuliahan secara online juga akan menurun. Oleh karena itu, tujuan dari penelitian ini adalah untuk menganalisis level metakognisi mahasiswa selama perkuliahan online yang telah dilaksanakan. Peneliti menggunakan pendekatan penelitian deskriptif kualitatif dengan metode pengisian form online. Subjek penelitian adalah 120 mahasiswa yang telah mengikuti kuliah online minimal 8 kali pertemuan atau 2 bulan. Hasil penelitian menunjukkan bahwa 83 mahasiswa berada pada tingkat metakognisi terendah (Tacit Use). Sedangkan siswa yang berada pada level metakognisi tertinggi sebanyak 2 siswa (Reflective Use). Dengan demikian peneliti dapat menyimpulkan bahwa tingkat metakognisi mahasiswa selama perkuliahan online masih sangat rendah.